(untitled) (Bangladesh Journal of Plant Taxonomy, 2016)
From three farming stages of Arthrospira platensis (Nordstedt) Gomont [Spirulina platensis (Gomont) Geitler], seven fungal species, namely, Cladosporium varians Braun, Melnik & K. Schub., Fusarium trichothecioides Wollenw., Geotrichum candidum Link, Mucor circinelloides Tiegh., M. hiemalis Wehmer, Penicillium frequentans Westling and Verticillium albo-atrum Reinke & Berthold were recorded for the first time from Bangladesh. Bangladesh J. Plant Taxon. 23(1): 1-6, 2016 (June)